Pengaruh penggunaan Artificial Intelligence (AI) terhadap potensi akademik mahasiswa psikologi Universitas Islam Raden Rahmat Malang - Atik Anawati; Rr. Hesti Setyodyah Lestari (Psikodinamika: Jurnal Literasi Psikologi, 2026)
This study aims to determine the effect of the use of Artificial Intelligence (AI) applications, specifically ChatGPT, on the academic potential of students in the Psychology Study Program at Raden Rahmat Islamic University, Malang. This study used a descriptive quantitative approach by applying basic linear regression analysis. Using the Slovin algorithm, a sample of 197 respondents was selected from 387 students who were part of the study population. Data were obtained using a Likert scale questionnaire and evaluated using validity, reliability, and classical assumption tests using SPSS. The study findings showed that the research instrument was declared valid and reliable with a Cronbach's Alpha value above 0.8. The data also met the requirements for normality, linearity, and homogeneity. The results of the regression test produced the equation Y = 12.384 + 0.652X with a significance value of 0.000 (<0.05) and a coefficient of determination (R²) of 0.433. This means that the use of ChatGPT has a positive and significant impact on students' academic potential, contributing 43.3%, while the remainder is due to other factors outside the study. This finding suggests that the more frequently students use ChatGPT appropriately, the greater their academic potential. ChatGPT helps students understand the material, think critically, and write in a more structured manner. However, its use requires responsibility to avoid diminishing originality and independent thinking skills.